Environmental Enrichment Improves Vestibular Oculomotor Learning in Mice - van der Geest, Jos N.; Spoor, Marcella; Frens, Maarten A. (Frontiers in Behavioral Neuroscience, 2021)
We assessed the behavioural effects of environmental enrichment on contrast sensitivity, reflexive eye movements and on oculomotor learning in mice that were housed in an enriched environment for a period of 3 weeks. Research has shown that a larger cage and a more complex environment have positive effects on the welfare of laboratory mice and other animals held in captivity. It has also been shown that environmental enrichment affects various behaviour and neuro-anatomical and molecular characteristics. We found a clear effect on oculomotor learning. Animals that were housed in an enriched environment learned significantly faster than controls that were housed under standard conditions. In line with existing literature, the enriched group also outperformed the controls in behavioural tests for explorative behaviour. Meanwhile, both visual and reflexive oculomotor performance in response to visual and vestibular stimuli was unaffected. This points towards an underlying mechanism that is specific for motor learning, rather than overall motor performance.